Review of wireless body sensor networks - Sulaiman Wali, Sondous; Najm Abdullah, Mohammed (International Journal of Engineering and Technology, 2020)
Wireless body area networks (WBANs) are emerging as important networks that are applicable in various fields. WBAN gives its users access to body sensor data and resources anywhere in the world with the help of the internet. These sensors offer promising applications in areas such as real-time health monitoring, interactive gaming, and consumer electronics. WBAN does not force the patient to stay in the hospital which saves a lot of physical movement. This paper reviews a review of WBANs. We study the following: prior researches, applications and architectures of WBAN, and compression sensing techniques.Â Â